MINAT SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI DI SMPN 1 MAJALAYA - Sri Ayu Lestari; Andrie Chaerul; Akhmad Dimyati (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
ABSTRACT This research is motivated by the not yet optimal learning of physical education at SMPN 1 Majalaya, Karawang Regency. This study aims to see the interest of students in participating in physical education learning at SMPN 1 Majalaya, Karawang Regency. To answer the problem formulation, researchers used a quantitative approach and survey methods. This research was conducted at SMPN 1 Majalaya Karawang by taking 4 classes or all VIII grade students recorded at SMPN 1 Majalaya, Karawang Regency who were included in 189 students as the research sample. The instrument used was a questionnaire. The analysis technique used is to pour the frequency into a percentage. The results of this study indicate that the students 'interest in participating in physical education learning at SMPN 1 Majalaya, Karawang Regency is in a very high category with 155 students' interest or 82.0%. Student interest in participating in physical education learning at SMPN 1 Majalaya, Karawang Regency, student interest in the very high category 155 students or 82.0%, high 10 students or 5.3%, moderate 1 student or 0.53% low 18 students 9.5%, very low 5 students or 2.6%. Keywords: Interests, Physical Education